"A Recipe for a Brick": The Pale King in Progress. Issue 4 (8th August 2017) - Groenland, Tim
ABSTRACT: This essay argues for the relevance of the ideas and critical vocabulary of genetic criticism to the study of David Foster Wallace's drafts. I read Wallace's manuscripts of the unfinished posthumous novel The Pale King through concepts taken from genetic and textual theorists in order to illuminate the relationship between the dynamics of textual development and the work's thematic interest in process and incompletion. I argue that the compositional processes behind the drafts of his final novel can be productively read alongside the increasing presence of metafiction in the work. The process of revision emerges as a textual influence in its own right, and the dialogic nature of Wallace's fiction emerges as, in part, a response to the writing process itself.